METODE PEMBELAJARAN SENI MUSIK DRUM DALAM MENINGKATKAN DAYA INGAT KELOMPOK B DI RA MIFTAHUL ULUM PANDANARUM - Wahdania Wahdania; Jihan Kusumawardhani (STAI Nusantara Banda Aceh, 2026)
This research is based on the lack of memory retention among children during drum band practice, which is caused by their limited focus on the art of drum music. As a result, some students experience reduced memory abilities in playing drum music.The pu rpose of this research is to explore the learning methods of drum music in enhancing memory among Group B students at RA Miftahul Ulum Pandanarum. This is a qualitative study using a naturalistic approach, as the research was conducted in a natural setting. The population of the study includes children from Group B of RA Miftahul Ulum Pandanarum. Data was collected through observation, interviews, and documentation. The results of this study concluded that the methods applied were 5 methods, namely: 1) Lecture or storytelling method, 2) Demonstration method, 3) Imitation method, 4) Drill or exercise method, 5) Whiteboard method. In addition to the 5 methods that need to be known for a trainer is the attitude of a trainer that must be maintained and the trust of a teacher at the child stage. Then, memorization does not need to be considered because memory must be memorized. At RA Miftahul Ulum, repetition is carried out 5 times and provides an estimated time of 15 minutes each time practicing with 1 break in between. This method is very effective for children and is responded to very well by children.